Common CP-OFDM transceiver design for low-complexity frequency domain equalization - Zegrar, Salah Eddine; Arslan, Hüseyin (IEEE-Institute of Electrical and Electronics Engineers Inc., 2022)
Common cyclic prefix-orthogonal frequency-division multiplexing (CCP-OFDM) groups multiple OFDM symbols and uses one CP to protect them in slow time-variant channels. However, due to this particular design of CCP-OFDM systems, complex time-domain estimation algorithms are used to estimate and equalize the channel, such as maximum likelihood (ML) estimators. In this letter, we propose a novel CCP-OFDM transceiver design enabling low-complexity frequency-domain channel estimation and equalization. Simulations under frequency selective channels have validated the effectiveness of the proposed scheme in terms of computational complexity, normalized mean squared error (NMSE), and bit error rate (BER).
Keywords: Common CP-OFDM; Channel Estimation; Frequency-Domain Equalization; Computational Complexity